ANALISIS HUKUM PENGGUNAAN BIOMETRIC VERIFICATION PADA LAYANAN PERBANKAN DIGITAL - Djamal Efendi; Hasnah Aziz; Ervawati; Dede Agus Sodikin; Dian Retno Widayati (CV. Lafadz Jaya, 2026)
Digital transformation in the banking sector has produced significant innovation in the form of biometric verification as an authentication mechanism in digital banking services. Biometric technology that includes facial recognition, fingerprints, iris scanning, and voice patterns offers a superior level of security and convenience compared to conventional authentication methods. However, the use of biometric verification raises fundamental legal complexities related to personal data protection, bank liability for system failures, and compliance with financial regulations and consumer protection. This article aims to analyze juridically the legal framework for the use of biometric verification in digital banking services in Indonesia. The research method used is qualitative with a normative-empirical legal approach. Data was collected through studies of legislation, regulator policies, industry reports, and scientific literature studies. The results show that the use of biometric verification faces multidimensional juridical challenges including regulatory weaknesses that do not comprehensively regulate biometric technology aspects, ambiguity in the distribution of responsibility between banks and customers for authentication failures, and limited mechanisms for protecting customers from biometric data misuse. This article recommends the need for harmonization of legislation, strengthening of biometric technology security standards, and development of proportional accountability mechanisms to create a safe and fair digital banking ecosystem.